2016
DOI: 10.1007/s00381-016-3167-2
|View full text |Cite|
|
Sign up to set email alerts
|

Intracranial germ cell tumors: a multi-institutional experience from three tertiary care centers in India

Abstract: This is the first multicentric study from India establishing that incidence of CNS GCT in India is similar to that in the West and differs from that in East Asian countries. However, similar to both, germinoma is the commonest histological type, and pineal location is most frequent. Studies on molecular alterations based on ethnicity and geographical location are necessary to provide clarity on differences in incidence. Attention needs to be focused on decreasing treatment heterogeneity and minimizing treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
4
16
1
Order By: Relevance
“…These data were similar to the ratio in a Japanese study. The sex ratio in this study was higher than that in a US study and an Indian study (1.54e2.4), 14,15 but slightly lower than that in a Korean study and a previous Taiwanese study (3.42 and 4, respectively). 8,16 Some differences may have occurred owing to ethnic differences.…”
Section: Discussioncontrasting
confidence: 82%
“…These data were similar to the ratio in a Japanese study. The sex ratio in this study was higher than that in a US study and an Indian study (1.54e2.4), 14,15 but slightly lower than that in a Korean study and a previous Taiwanese study (3.42 and 4, respectively). 8,16 Some differences may have occurred owing to ethnic differences.…”
Section: Discussioncontrasting
confidence: 82%
“…Intracranial GCTs are the most common brain tumours in the paediatric and adolescent population, with incidence rates differing among the various ethnic groups 11 . There is a higher incidence in Asia and Pacific Islanders, comprising 8%‐15% of all childhood brain tumours from a series in Taiwan, Japan and Korea vs 0.1%‐3% in the North America and Europe 30‐34 . The reasons for these differences may be related not only to the genetic predisposition in the Asian population, but also to different patient definitions and tumour classifications 32,33 .…”
Section: Suprasellar Germinomamentioning
confidence: 99%
“…[ 7 8 ] Recently, a multi-institutional study, comprising the data from three institutions in India, reported that the GCT accounted for 0.43% of CNS tumors. [ 9 ] Further, a review of management strategies of these tumors over a long time and their evolution will aid in better management of these tumors. The present study, the largest single institutional study from India, to the best of our knowledge, attempts to document the proportion of GCTs managed in a tertiary neurosurgical institute over a period of 16 years, identify the pathological spectrum, and correlate clinically and elaborate on the management strategies of these patients.…”
Section: Introductionmentioning
confidence: 99%